A Grammar of Coastal Marind - Olsson, Bruno (Mouton grammar library ;, 2021)
This grammar provides the first modern, comprehensive description of Coastal Marind. It is a Papuan language spoken by the coastal-dwelling Marind-Anim, formerly expansionistic head-hunters of the Southern New Guinea lowlands. Like the other languages of the poorly known Anim family, Coastal Marind features astonishingly complex verb morphology and a range of unusual phenomena, including indexing of up to four arguments on the verb, verbal marking of focus (the 'Orientation' system), engagement prefixes tracking the attention of the addressee, and a system of four genders realised by intricate agreement patterns. The structure of the language is examined in a detailed but accessible way, and its many complexities are brought to life by contextualised spontaneous data, drawn from a rich audio-visual corpus.